2014
DOI: 10.1155/2014/925650
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Apolipoprotein B/Apolipoprotein A-I Ratio, Metabolic Syndrome Components, Total Cholesterol, and Low-Density Lipoprotein Cholesterol with Insulin Resistance in the Population of Georgia

Abstract: The study was designed to assess the association between insulin resistance (IR) and apolipoprotein B/apolipoprotein A-I ratio (ApoB/ApoA-I ratio), metabolic syndrome (MetS) components, total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) in the nondiabetic population of Georgia. The subjects were 1522 Georgians of Caucasian origin (mean age = 45 years, 653 women) without diabetes who had visited the clinics for a related health checkup between 2012 and 2013. IR was calculated using the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In addition, some researchers reported that IR can promote NAFLD development by inducing TG decomposition of within adipose tissue and simultaneously enhancing TG synthesis in the liver [ 41 , 42 ]. On contrary, IR emergence accelerates sugar decomposition, leading to an enhancement in blood glucose and VLDL, which then promotes the release of excessive TC into the blood, thus raising serum TC levels [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some researchers reported that IR can promote NAFLD development by inducing TG decomposition of within adipose tissue and simultaneously enhancing TG synthesis in the liver [ 41 , 42 ]. On contrary, IR emergence accelerates sugar decomposition, leading to an enhancement in blood glucose and VLDL, which then promotes the release of excessive TC into the blood, thus raising serum TC levels [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study in Georgia revealed that insulin resistance (HOMA-IR) was positively correlated with age, apoB, apoB/apoA-I ratio, metabolic syndrome components (excluding HDL-C), LDL-C, fasting insulin, and TC and negatively correlated with HDL-C and apoA-I in both genders. In the logistic regression models, gender, age, apoB/apoA-I ratio, diastolic pressure, HDL-C, LDL-C, FBG, and TG were the covariates significantly associated with IR 13. Environmental factors such as smoking influenced the lipid profile (by aggravating atherogenic dyslipidemia) in subjects with insulin resistance 14.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the plasma concentration of ApoB indicates the total number of potentially atherogenic particles, correlating with the non-HDL-C levels. The ApoB/ApoA ratio is a better indicator of the risk of coronary artery disease compared to LDL-C. A study reported that physical activity can effectively decrease body fat percentage, and increased ApoB metabolism can affect LDL metabolism (25). Variation in circulating concentrations of factors such as lecithin cholesterol acyltransferase, acyl-CoA cholesterol acyltransferase, cholesteryl ester transfer protein, and phospholipid transfer protein due to exercise activity can affect the concentration of ApoA (26).…”
Section: / Moazami and Askarimentioning
confidence: 99%